Modulatory effects of brain-derived neurotrophic factor Val66Met polymorphism on prefrontal regions in major depressive disorder. (May 2015) - Legge, Rebecca MacGregor; Sendi, Shahbaz; Cole, James H.; Cohen-Woods, Sarah; Costafreda, Sergi G.; Simmons, Andrew; Farmer, Anne E.; Aitchison, Katherine J.; McGuffin, Peter; Fu, Cynthia H. Y.
Abstract : Background: Brain-derived neurotrophic factor (BDNF) Val66Met polymorphism contributes to the development of depression (major depressive disorder, MDD), but it is unclear whether neural effects observed in healthy individuals are sustained in MDD. Aims: To investigate BDNF Val66Met effects on key regions in MDD neurocircuitry: amygdala, anterior cingulate, middle frontal and orbitofrontal regions. Method: Magnetic resonance imaging scans were acquired in 79 persons with MDD (mean age 49 years) and 74 healthy volunteers (mean age 50 years). Effects on surface area and cortical thickness were examined with multiple comparison correction. Results: People who were Met allele carriers showed reduced caudal middle frontal thickness in both study groups. Significant interaction effects were found in the anterior cingulate and rostral middle frontal regions, in which participants in the MDD group who were Met carriers showed the greatest reduction in surface area. Conclusions: Modulatory effects of the BDNF Val66Met polymorphism on distinct subregions in the prefrontal cortex in MDD support the neurotrophin model of depression.